Implementation of the State of Law Principles from the Constitutional Law Perspective: A Case Study of Legislative Aspects in Law Enforcement in Indonesia - Pakpahan, Zainal Abidin; Yasmin, Ananda Sabillah; Safitri, Indri Tiya; Nainggolan, Elian S Christoper; Nasution, Thorique Akbar Maulana (Universitas Sumatera Utara, 2024)
The Fourth Amendment to the 1945 Constitution of the Republic of Indonesia, enacted in 2002, officially established the concept of the State of Law, or